2016
DOI: 10.2967/jnumed.115.167403
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Tracing of NMDA and GABA-A Receptors in Rat Brain After Traumatic Brain Injury Using 18F-GE-179 and 18F-GE-194 Autoradiography

Abstract: In vivo imaging of N-methyl-D-aspartate (NMDA) glutamate receptor and γ-aminobutyric acid (GABA)-A receptor during progression of brain pathology is challenging because of the lack of imaging tracers with high affinity and specificity. Methods: We monitored changes in NMDA receptor and GABA-A receptor in a clinically relevant model of traumatic brain injury (TBI) induced by lateral fluid percussion in adult rats, using 2 new ligands for PET: 18 F-GE-179 for the open/active state of the NMDA receptor ion channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The microdialysis assay showed that extracellular glutamate levels were significantly elevated in WT brains, while the increases were diminished in the HIF‐1α −/− brains (Figure B). To observe the glutamate receptor activation, a radiotracer, 18 F‐labelled alkylthiophenyl guanidine ( 18 F‐FSAG or 18 F‐GE‐179), which binds to the phencyclidine (PCP) site of the N ‐methyl‐ d ‐aspartate (NMDA) channel , was synthesized for observing the activation of NMDA receptor (NMDAR) in vitro and in vivo . Positron emission tomography (PET) imaging and magnetic resonance imaging (MRI) studies showed a high accumulation of 18 F‐FSAG in infraction area, and 18 F‐FSAG uptake reached a steady state at 30 min after injection in WT mice with or without CIR (see supplementary material, Figure S1A, B).…”
Section: Resultsmentioning
confidence: 99%
“…The microdialysis assay showed that extracellular glutamate levels were significantly elevated in WT brains, while the increases were diminished in the HIF‐1α −/− brains (Figure B). To observe the glutamate receptor activation, a radiotracer, 18 F‐labelled alkylthiophenyl guanidine ( 18 F‐FSAG or 18 F‐GE‐179), which binds to the phencyclidine (PCP) site of the N ‐methyl‐ d ‐aspartate (NMDA) channel , was synthesized for observing the activation of NMDA receptor (NMDAR) in vitro and in vivo . Positron emission tomography (PET) imaging and magnetic resonance imaging (MRI) studies showed a high accumulation of 18 F‐FSAG in infraction area, and 18 F‐FSAG uptake reached a steady state at 30 min after injection in WT mice with or without CIR (see supplementary material, Figure S1A, B).…”
Section: Resultsmentioning
confidence: 99%
“…The stimulation apparently provoked an increase in the grey matter V T from about 3.5 mL g −1 to 5 mL g −1 , in the absence of any effect on perfusion as measured by [ 15 O]-water PET in the same session. Autoradiographic studies ex vivo with [ 18 F]GE-179 ( 38 ) showed persistent increases in binding in rat cerebral cortex after traumatic brain injury, which were interpreted to indicate activation of NMDA receptors in the injured tissue [ 63 ].…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…The diarylguanidine analog, [123I]-CNS-1261 exhibited limited success in a clinical study of patients with schizophrenia (207). In PET imaging, despite encouraging results (208), a recent preclinical study using [18F]GE-179 was unable to demonstrate displaceable in vivo binding that would have been evidence of an in vivo activity-dependent NMDA signal in rats and primates (209211). Recently, a new [18F]-labeled derivative of memantine, [18F]-fluoroethylnormemantine ([18F]-FNM), was synthesized.…”
Section: Glutamate Receptorsmentioning
confidence: 99%